Clinical cases of SYSADOA use in complex conservative therapy of patients with knee osteoarthritis - O. A. Kaplunov; K. O. Kaplunov (Лечащий Врач, 2021)
The article discusses the validity and the effectiveness of the use of symptomatic slow-acting drugs for osteoarthritis (SYSADOA) in the treatment of patients with clinically pronounced stages of knee osteoarthritis (II-III degrees according to the Kellgren–Lawrence classification), developed at different ages under different comorbid circumstances. The aim of the study was to evaluate the effect of the use of Alflutop as part of complex therapy in relation to the functional status of the affected joint at the 4th week of the follow-up. In the first case, it was anamnestically established that the patient had an immediate allergic reaction to repeated intra-articular administration of hyaluronic acid derivatives two years earlier, and GCS (glucocorticosteroids) could not be used due to the risk of recurrence of osteomyelitis. In the second case, an elderly man with severe somatic pathology (type 1 diabetes, bronchial asthma) was diagnosed with a clinically pronounced stage of gonarthritis (grade III according to Kellgren–Lawrence), the use of SYSADOA was preceded by 3 two-week courses of conservative therapy using hyaluronic acid derivatives in combination with intra-articular corticosteroids, while significant results could not be achieved. Finally, in the third case, a man with a history of idiopathic purulent gonarthritis was contraindicated to the injectable forms of GCS, and for socio-economic reasons it was not possible to use hyaluronates. Considering these circumstances, the combination of NSAIDs + SYSADOA was used in all the above mentioned cases (at the start – intra-articular, then intramuscularly). As a result of studying the clinical effectiveness of the proposed therapy regimen in patients with the presence of an arthritic component of the disease, positive results of the drug therapy were established: by the end of the course of therapy, the amplitude of movements and the severity of the pain syndrome showed more significant positive changes vs laboratory parameters. Given the impossibility of using derivatives of HA, as well as GCS, the use of a SYSADOA in our comorbid cases is the only possible component of an effective complex conservative therapy for knee osteoarthritis.